Konwersacyjne nacechowanie stylistyczne jako sygnał więzi wspólnotowych na materiale kazań dziewiętnastowiecznych Józefa Męcińskiego = Conversational stylistic marking as a sign of the community ties on the material of sermons by Joseph Męciński (XIX c.) - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the paper is the use of the pronoun grammatical category in sermons as a way of expressing community ties. The research material is based on "Preaching speeches in various church services (especially the parish) circumstances" by Joseph Męciński (Krakow 1808).
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie